2021
DOI: 10.1007/s00784-021-04276-x
|View full text |Cite
|
Sign up to set email alerts
|

Including dental professionals in the multidisciplinary treatment team of head and neck cancer patients improves long-term oral health status

Abstract: Objective To assess in a cross-sectional study the impact of including dental professionals in the multidisciplinary treatment team of head and neck squamous cell carcinoma (HNSCC) patients on the long-term oral health status. Materials and methods Oral health status, dental care behaviours, and oral health–related quality of life were assessed based on a clinical and radiographic examination, interview, and medical records in patients treated for HNSCC ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…There are only limited data at which rate required dental treatment recommendations are subsequently implemented. As Bertl et al reported that about 90% of patients followed dental recommendations involving a multidisciplinary treatment team, we may assume that in most of our patients' recommendations before radiotherapy we mostly adequately followed (Bertl et al, 2022 ).…”
Section: Discussionmentioning
confidence: 95%
“…There are only limited data at which rate required dental treatment recommendations are subsequently implemented. As Bertl et al reported that about 90% of patients followed dental recommendations involving a multidisciplinary treatment team, we may assume that in most of our patients' recommendations before radiotherapy we mostly adequately followed (Bertl et al, 2022 ).…”
Section: Discussionmentioning
confidence: 95%
“…The inclusion of dental health in the MDT meeting can be a simple yet effective way of bringing the attention to oral care 39 . This may be as in‐depth as the inclusion of an oral health professional to perform a dental screening as part of a CF annual review, to something as simple as ticking a dental checkbox by asking the question, “have they been to see a dentist this year”?…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of dental health in the MDT meeting can be a simple yet effective way of bringing the attention to oral care. 39 This may be as in-depth as the inclusion of an oral health professional to perform a dental screening as part of a CF annual review, to something as simple as ticking a dental checkbox by asking the question, "have they been to see a dentist this year"? These reminders will give an opportunity for all health professionals and patients to think about dental health and may also provide better confidence in the MDT to discuss dental health and become more familiar with referral processes.…”
Section: Health Professionals' Views On Improving Cf Dental Carementioning
confidence: 99%
“…This model is commonly implemented in high-level oncology hospitals or oncology departments within large general hospitals [11]. It represents a leading international standardized diagnosis and treatment model [14][15][16][17]. The second form refers to multidisciplinary consultations organized by relevant departments according to the needs of patients or their families.…”
Section: Introductionmentioning
confidence: 99%